Diagnostic utility of saline infusion doppler sonohysterography in endometrial mass lesions - (:unkn) unknown (PROFESSIONAL MEDICAL PUBLICATIONS, 2016)
Objective: To evaluate the importance of saline infusion Doppler sonohysterography (SIS-D) in the assessment of transvaginal ultrasound (TVUSG)-suspected intrauterine mass lesions in women complaining about abnormal uterine bleeding with respect to hysteroscopy (H/S) and pathologic diagnosis. Methods: This study was conducted on patients, who visited to our clinic with abnormal uterine bleeding and whose TVUSGs indicated intrauterine masses. The study covered a total of 100 patients. SIS-D and hysteroscopy were performed on those 100 patients. SIS-D results were compared with hysteroscopy results. The relation between SIS-D findings and pathology results were evaluated. Results: For SIS; specificity was 96%, sensitivity was 60%, positive predictive value (PPV) was 87.8%, negative predictive value (NPV) was 83.3%, and the accuracy rate was 87%. For TVUSG; PPV was 75%. According to SIS-D, 92.2% of the lesions that had single-vessel feeding patterns were endometrial polyps, and this was statistically significant (p<0.0001). 57.1% of the lesions that had multiple-vessel feeding patterns were submucous myomas, and this was statistically significant (p<0.0001). Conclusion: SIS should be performed in patients before hysteroscopy because it will protect a considerable number of patients from unnecessary invasive procedures. SIS-D gives an idea on the histopathology of the mass.
Keywords: Saline infusion doppler sonohysterography; Hysteroscopy; Endometrial Mass Lesions; TRANSVAGINAL SONOGRAPHY; POSTMENOPAUSAL WOMEN; SUBMUCOSAL FIBROIDS; HYSTEROSCOPY; POLYPS; ULTRASONOGRAPHY; PREMENOPAUSAL